THE RELATIONSHIP OF MOTHER'S EDUCATION AND OCCUPATION TO THE EVENTS OF UNDERWEIGHT IN TODDLERS - Muhammad Iqbal; Jun Musnadi Is; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Based on the 2019 SSGBI report, it was stated that the prevalence of underweight in toddlers, especially in Aceh province was 21.9%, West Aceh district was 24.5%. The high prevalence of underweight in Aceh Barat is certainly a public health problem that must be addressed so as not to adversely affect the quality of the nation's generation. Objective: to determine the relationship between education and mother's occupation on the incidence of underweight in toddlers in Kaway XVI sub-district. Methods: The design of this study was cross-sectional analytic. The population is mothers and toddlers aged 0-60 months in Kaway XVI sub-district. The number of respondents as many as 114 mothers and toddlers. The sample was selected using a purposive sampling technique. Data were collected using questionnaires and anthropometric measurements (BB/U) according to WHO standards. The data that has been collected were analyzed using univariate and bivariate analysis (chi-square test). Results: The results of the chi-square test showed that there was no significant relationship between mother’s education (p-value: 0.486; PR: 1.46; 95%CI: 0.492-4.433) and mother's occupation (p-value: 0.388; PR: 1.47; 95%CI : 0.561-4.396) to the incidence of underweight in toddlers.